EVALUASI SISTEM PERADILAN ANAK DALAM PERLINDUNGAN HAK ANAK - Ahmad Arif Fadilah; Radita Maharani; Siti Nur Haliza (Sindoro: Cendikia Pendidikan, 2024)
Human rights are rights that a person has and obtains at the time of his or her birth into social life. This right is fundamental and universal. applies to everyone without distinction of nation, race, religion, class or gender. It is a human right that every person must be given the opportunity to develop according to his talents and ideals. The normative legal concept states that humans have rights that are inherent to themselves because they are human. Human rights apply anytime, anywhere and to anyone, so they are universal. Human rights are in principle inalienable, indivisible, interconnected and interdependent. Human rights are usually addressed to the state, in other words, it is the state that has the obligation to respect, protect and fulfill human rights, including by preventing and following up on violations committed by the private sector. Human rights can be classified as civil and political rights relating to with civil liberties (e.g. the right to life, the right not to be tortured, and freedom of expression).